The Role of Customer Relationship Vulnerability in Service Recovery - Cenophat, Sadrac; Eisend, Martin; Bayón, Tomás; Haas, Alexander; Justus Liebig University Giessen (My University, 2024)
The effectiveness of service recovery initiatives has primarily been explained by exchange theories implicitly assuming that the customer desires beneficial relationships. The present research extends studies in this tradition by emphasizing the crucial role of the customer’s vulnerability. Drawing on crisis theory, we argue that the effectiveness of service recovery initiatives is contingent on customer relationship vulnerability (CRV), which is defined as a customer predisposition to psychological harm in relationships with service firms. The findings show that a full-service recovery is not always possible among vulnerable customers. We discuss the implications for theory and service management practice.
Keywords: ddc:330